Effects of Dairy Farm Training: A Path Analysis (Indian Journal of Extension Education, 2021)
The study was conducted to ascertain the direct and indirect effects of training on knowledge, adoption, and income of trained dairy farmers in comparison to non-trainees. The propensity score matching method was used to avoid selection bias and build a statistical comparison group. A trained group of dairy farmers was significantly higher in knowledge and adoption of scientific dairy practices. Trained farmers were generating twice the net annual income from dairy farming than the un-trained dairy farmers. Training participation significantly contributed in predicting knowledge and positively influenced adoption and income. The path analysis indicated that entrepreneurial behaviour was the most crucial variable that directly and indirectly affected knowledge. Entrepreneurial behaviour affected adoption, most directly, while attitude towards dairy farming affected adoption, most indirectly. Net annual income was most directly affected by dairy herd size and largely through the landholding of the respondents. The results suggest that organization of dairy farmers’ training by moulding their entrepreneurial behaviour, attitude, and economic motivation would be more effective in achieving a desirable outcome.